Experimental Semiotics: A Review - Galantucci, Bruno; Garrod, Simon (Frontiers in Human Neuroscience, 2011)
In the last few years a new line of research has appeared in the literature. This line of research, which may be referred to as experimental semiotics (Galantucci, 2009; Galantucci & Garrod, 2010), focuses on the experimental investigation of novel forms of human communication. In this review we will (a) situate experimental semiotics (henceforth ES) in its conceptual context, (b) illustrate the main varieties of studies thus far conducted by experimental semioticians, (c) illustrate three main themes of investigation which have emerged within this line of research, and (d) consider implications of this work for cognitive neuroscience.